Correlation Between Female Junior High School Students Knowledge And BSE Behaviour - Karni, Winda Ayu Juwita; Rostianingsih, Dewi; Irmawaty Sirait, Lenny (Genius Midwifery Journal, 2024)
Introduction: Breast cancer often presents as a painless lump and can develop, invade surrounding breast tissue, and spread to nearby lymph nodes or other organs in the body. The high mortality rate of breast cancer is due to a lack of knowledge about the disease and the importance of early detection, leading to many patients seeking medical help at a late stage. According to Globocan data from 2020, teenage cancer patients in Indonesia rank 3rd in Asia. The government recommends Breast Self-Examination (BSE) as the most effective screening method. BSE is very easy to perform, yet many teenagers are unaware of this method. Objective: The review is to summarize the correlation between students knowledge and BSE Behaviour. Method: The study used a descriptive quantitative design with a cross-sectional approach and a simple random sampling technique. The sample size was 141 students, and the chi-square statistical test was used for analysis. Result: The majority, 91.5%, of Ananda Junior High School students had never performed BSE and had poor knowledge about the pathophysiology of breast cancer (93.6%) and breast cancer prevention (83.7%). A p-value of 0.000 (p < 0.05) was obtained, indicating a significant correlation between knowledge about the pathophysiology and prevention of breast cancer and BSE behavior. Conclussion: The proportion of Ananda Bekasi Junior High School students who engage in BSE behavior is very low (8.5%). Most respondents had poor knowledge about the pathophysiology of breast cancer (93.6%) and breast cancer prevention (83.7%).